Substantial Targeting Advantage Achieved by Pulmonary Administration of Colistin Methanesulfonate in a Large-Animal Model - Landersdorfer, Cornelia B. (Antimicrob Agents Chemother, 2016)
Colistin, administered as its inactive prodrug colistin methanesulfonate (CMS), is often used in multidrug-resistant Gram-negative pulmonary infections. The CMS and colistin pharmacokinetics in plasma and epithelial lining fluid (ELF) following intravenous and pulmonary dosing have not been evaluated in a large-animal model with pulmonary architecture similar to that of humans. Six merino sheep (34 to 43 kg body weight) received an intravenous or pulmonary dose of 4 to 8 mg/kg CMS (sodium) or 2 to 3 mg/kg colistin (sulfate) in a 4-way crossover study. Pulmonary dosing was achieved via jet nebulization through an endotracheal tube cuff. CMS and colistin were quantified in plasma and bronchoalveolar lavage fluid (BALF) samples by high-performance liquid chromatography (HPLC). ELF concentrations were calculated via the urea method. CMS and colistin were comodeled in S-ADAPT. Following intravenous CMS or colistin administration, no concentrations were quantifiable in BALF samples. Elimination clearance was 1.97 liters/h (4% interindividual variability) for CMS (other than conversion to colistin) and 1.08 liters/h (25%) for colistin. On average, 18% of a CMS dose was converted to colistin. Following pulmonary delivery, colistin was not quantifiable in plasma and CMS was detected in only one sheep. Average ELF concentrations (standard deviations [SD]) of formed colistin were 400 (243), 384 (187), and 184 (190) mg/liter at 1, 4, and 24 h after pulmonary CMS administration. The population pharmacokinetic model described well CMS and colistin in plasma and ELF following intravenous and pulmonary administration. Pulmonary dosing provided high ELF and low plasma colistin concentrations, representing a substantial targeting advantage over intravenous administration. Predictions from the pharmacokinetic model indicate that sheep are an advantageous model for translational research.